The role of Northeast Pacific meltwater events in deglacial climate change - Praetorius, Summer K.; Condron, Alan; Mix, Alan C.; Walczak, Maureen H.; McKay, Jennifer L.; Du, Jianghui (Science Advances, 2020)
Columbia River megafloods occurred repeatedly during the last deglaciation, but the impacts of this fresh water on Pacific hydrography are largely unknown. To reconstruct changes in ocean circulation during this period, we used a numerical model to simulate the flow trajectory of Columbia River megafloods and compiled records of sea surface temperature, paleo-salinity, and deep-water radiocarbon from marine sediment cores in the Northeast Pacific. The North Pacific sea surface cooled and freshened during the early deglacial (19.0-16.5 ka) and Younger Dryas (12.9-11.7 ka) intervals, coincident with the appearance of subsurface water masses depleted in radiocarbon relative to the sea surface. We infer that Pacific meltwater fluxes contributed to net Northern Hemisphere cooling prior to North Atlantic Heinrich Events, and again during the Younger Dryas stadial. Abrupt warming in the Northeast Pacific similarly contributed to hemispheric warming during the Bølling and Holocene transitions. These findings underscore the importance of changes in North Pacific freshwater fluxes and circulation in deglacial climate events. Deglacial meltwater input to the North Pacific contributed to abrupt Northern Hemisphere climate events. Deglacial meltwater input to the North Pacific contributed to abrupt Northern Hemisphere climate events.